Tym9n
Rozwiązane

Pomoże ktoś z tymi przykładami?
Z góry dziękuje
(-3) x 0,2
6 x (-1/3)
(-1,3) x (-2)
(-9) x (-1/2)
(-2/7) x 7/12
(-12) : 6
(-4) : (-8)
3,2 : (-2)
(-3/4) : 1/4
(-0,1) do potęgi 2
(-2) do potęgi 3
(-1/2) do potęgi 4



Odpowiedź :

Odpowiedź:

Odpowiedź w załączniku.

Liczę na naj :)

Zobacz obrazek Miaq134

Odpowiedź:

(-3) × 0,2 = (-0,6)

6 × (-1/3) = (-2)

(-1,3) × (-2) = 2,6

(-9) × (-1/2) = 9/2 = 4,5

(-2/7) × 7/12 = (-1/6)

(-12) : 6 = (-2)

(-4) : (-8) = 4/8 = 1/2

3,2 : (-2) = (-1,6)

(-3/4) : 1/4 = (-3/4) × 4 = (-4)

(-0,1)² = 0,01

(-2)³ = (-8)

(-1/2)⁴ = 1/16